Posiedzenie przygotowawcze jako konsensualna forma zakończenia postępowania cywilnego - Budniak-Rogala, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Preparatory hearing is a principal institution of organisation of civil procedure (Article 205¹ et seq. of the Civil Procedure Code). Provisions regarding the hereinabove mentioned matter have been entered into the Code of Civil Procedure pursuant to act of 4th of July 2019, which came into force (in that regard) on 7th of November 2019. Solutions implemented by the legislator are, above all, aimed at expediting the procedure and preventing its excessive length. Preparatory hearing is designed to fulfil these objectives. It is beyond dispute that preparatory hearing is a consensual form of termination of civil procedure. (I) Firstly, solutions implemented by the legislator constitute a conciliate character of preparatory hearing. It is indicated by (1) the main purpose of preparatory hearing (2) reflected in its designed course, as well as (3) a particular role of a judge presiding over said hearing. (II) Secondly, as a consequence there are some additional mechanisms aimed at holding the hearing in question connected with (1) mandatory participation in the hearing and (2) informalisation of its course. (III) Thirdly and finally, during the hearing presiding judge may refer the parties to mediation. While interpreting the provisions on the analysed hearing a fundamental question occurs. Are the solutions implemented by the legislator an adequate response to current practises and whether they will be actually applied by courts. Provisions concerning preparatory hearing (Articles 205 ⁴ to 205⁸ of the Civil Procedure Code) indicate many positive aspects connected with fulfilling regulation aiming at expediting the procedure and preventing its excessive length. However, the analysed provisions have significant defects, which may relevantly affect their implementation. Ultimately, it is worth considering that based on the objectives of the legislator, the implementation of institution in question should be generally mandatory (vide Article 205⁴ § 1 of the Civil Procedure Code). In justified cases a preparatory hearing may not be called (cf. Article 205⁴ § 3 of the Civil Procedure Code). As a consequence, this solutions raises significant doubts whether (taking into consideration Polish judicial reality) the institution of preparatory hearing shall, as a result, become a dead one.
Keywords: organisation of the procedure